Peran Komunikasi Interpersonal Keluarga dalam Menggali Potensi Individu Berkebutuhan Khusus untuk Mandiri dan Berdaya - Setyaningtyas, Emilya; Yulianti, Wulan; Hery, Della Melianie (TIN: Terapan Informatika Nusantara, 2024)
The Chairperson of the National Commission on Disability revealed that there is still a negative stigma towards individuals with special needs. This is reflected in several incidents where individuals with special needs experienced rejection and inappropriate treatment. Twenty-three cases of special protection of children with special needs were reported to the Indonesian Child Protection Commission (KPAI). Handling individuals with special needs has its challenges, especially when entering adulthood, where parents have an essential role as educators, managers, and mentors. Interpersonal communication is one form of communication that is important to use within the family. Individuals with special needs often have difficulty processing language literally and face barriers in speaking and communicating. As the closest party, the family should be able to apply interpersonal communication well with people with special needs, but many cases still occur. This study aims to review the role of family interpersonal communication in developing the potential of individuals with special needs to be independent and productive. The approach used in this research is qualitative with descriptive methods by collecting data through in-depth interviews and focus group discussions (FGDs). The findings in this study show that all dimensions of the role of interpersonal communication have been implemented by families, who are the primary key to developing their children's potential as individuals with special needs to be independent and productive. The results showed that it is undeniable that, as humans, family members can also have frustrations and even need special handling to be ready to have a family as individuals with special needs. All family members help each other and have a harmonious relationship, and a sense of perseverance is formed from the collaboration of fellow families who experience similar experiences. Social media can be a medium for individuals with special needs to show their talents as independent individuals.